1991
DOI: 10.1029/91jc02123
|View full text |Cite
|
Sign up to set email alerts
|

Use of satellite scatterometer winds to force an ocean general circulation model

Abstract: The present study is an attempt to evaluate the capacity of scatterometer wind data to be provided by the forthcoming European Remote Sensing 1 (ERS 1) and NASA Scatterometer (NSCAT) satellite missions, to successfully force basin scale ocean circulations. The mid‐latitude ocean is simulated with a three‐layer, quasi‐geostrophic, eddy‐resolving model in a square box geometry. The variable wind stress, which is used to simulate scatterometer winds, is derived from European Centre for Medium‐Range Weather Foreca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The methodology of data processing is given by Liu et al [1998]. Here we are not concerned with the accuracy of the NSCAT data and the impact of sampling strategy, which have been the focus of many other studies [e.g., Barnier et al, 1991Barnier et al, , 1994Bourassa et al, 1997]. Suffice it to say that the NSCAT wind product is probably the best resolved wind data set available and its quality is sufficient for the purpose of this study.…”
Section: Data and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology of data processing is given by Liu et al [1998]. Here we are not concerned with the accuracy of the NSCAT data and the impact of sampling strategy, which have been the focus of many other studies [e.g., Barnier et al, 1991Barnier et al, , 1994Bourassa et al, 1997]. Suffice it to say that the NSCAT wind product is probably the best resolved wind data set available and its quality is sufficient for the purpose of this study.…”
Section: Data and Modelmentioning
confidence: 99%
“…They found that the mean and eddy kinetic energies could be enhanced by up to an order of magnitude in the eastern basin of the North Atlantic when the high-wavenumber forcing was applied. The sensitivity of ocean simulations to wind resolution has also been studied by investigators who were concerned with the impact of satellite scatterometer winds [Barnier et al, 1991[Barnier et al, , 1994.…”
Section: Introductionmentioning
confidence: 99%
“…They conclude that more modeling studies are required before their results can be generalized. The present study extends the investigation of Barnier et al [ 1991]. Here a similar study is conducted but using a quite different model and a denser time sampling of the wind (6 hours instead of 1 day).…”
Section: Introductionmentioning
confidence: 90%
“…In a recent study using scatterometer wind data simulated from daily analyses of ECMWF, Barnier et al [1991] show that within the framework of quasi-geostrophic (QG), midlatitude ocean models, scatterometer winds from NSCAT (and to a lesser degree from ERS-1) would be appropriate to 14,187 Wave speed is 316 cm s -1 for baroclinic mode 1, 149 cm s -1 for baroclinic mode 2, and 100 cm s for baroclinic mode 3. force an ocean model. However, they stressed that their results are dependent upon the numerical model used (midlatitude, quasi-geostrophic) and upon the original wind field from which scatterometer winds were simulated (i.e., daily analyses from ECMWF).…”
Section: Introductionmentioning
confidence: 99%